(3cTa GdcTGas - (3SQGL GdOjf CHh MaU YeQ Hf YHO GdQMef Hf YeQ GdbRhjfj, YeQ GdbRhjfj,J (B745 (3g` s
(3ChdgG (B:s
(3hHYO aEf YeQ Hf YHO GdQMef GdaGQSi jbhd CTGQ Edi ef dRefi Cf CMQQ ai GdcTa Yf eTcdGJ GdcTGa s
(3BNQgG (B:s
(3fLR JMQjQ GdfUa GdChd ef cTa GdcTGa hjJdhg GdfUa GdKGfiq s
(3GdLRA GdKGfj HQbe (B150 (3chjJs
(3HgG fXGe GdJYbjHIs
(3hQOJ fSHJg Ydi UaMI GdZdGa Edi YeQ GdHjVGhis
(3JHUQI GdYfhGf (B:s
(3JMTjI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs